Phosphite inhibits Phytophthora cinnamomi by downregulating oxidoreductases and disrupting energy metabolism - Prabhu, S. Ashok; Naicker, Previn; Duong, Tuan A.; Govender, Ireshyn Selvan; Engelbrecht, Juanita; Backer, Robert; Stoychev, Stoyan Hristov; van den Berg, Noëlani (Frontiers in Microbiology, 2025)
Phytophthora root rot caused by the hemibiotrophic oomycete, Phytophthora cinnamomi is a major biotic hindrance in meeting the ever-increasing demand for avocados. In addition, the pathogen is a global menace to agriculture, horticulture and forestry. Phosphite trunk injections and foliar sprays remain the most effective chemical management strategy used in commercial avocado orchards against the pathogen. Phosphite is known to counter P. cinnamomi both directly and indirectly through fortification of host defense. However, phosphite's direct mode of action is still not understood completely. This study identified a P. cinnamomi isolate GKB4 sensitive to phosphite (EC50 of 27.9 μg/mL) and investigated the direct impact of phosphite on this isolate through label-free quantitative SWATH-MS. Proteomics data analysis of untreated vs. phosphite-treated samples revealed that the xenobiotic affects the pathogen's growth by targeting the oxidoreductases whose abundance is significantly reduced. Further, perturbations in the energy metabolism and membrane/transmembrane proteins and transporters, and oxidative stress contribute to growth inhibition. The current study also identified increased putrescine biosynthesis, a polyamine, that when present at non-optimal concentrations could be cytostatic/cytotoxic. The differential expression of enzymes involved in the biosynthesis of secondary metabolites and the intermediates/precursors involved in their biosynthesis is an interesting finding that needs further investigation to ascertain their role in phosphite-induced stress. The pathogen's attempt to counter phosphite's growth-inhibitory effects—through upregulation of alternate bioenergetics pathways (amino acid catabolism and β-oxidation of fatty acids), mitochondrial translation and translocation machinery, peroxisomal proteins, and antioxidants—appears ineffective. This research furthers our limited understanding of the direct in vitro effects of phosphite on P. cinnamomi and has identified potential candidates for molecular functional investigation.